Efeitos de reguladores do metabolismo lipídico no desenvolvimento in vitro de embriões bovinos e na sobrevivência à vitrificação - Lima, Marina Ragagnin de [UNESP] (2015)
Embryos produced in vitro (IVP) have low survival to conventional cryopreservation methods. In attempt to improve the production and the rate of embryo survival to the cryopreservation process, was used the metabolic regulators, L-carnitine (CA), forskolina (FO) and the conjugated linoleic acid isomers trans-10, cis-12 (CLA), separately or in combination in different doses, starting the fourth (D4) or sixth (D6) days of the embryo culture development in vitro. In experiment 1, the best results of production (62,0 ± 12,5%, P = 0,02), expansion (60,7%, P = 0,009), and hatching (41,1 % P = 0,04) was obtained using 2,5 mM of CA. In experiment 2, the production of embryos was not influenced by supplementation with FO (P=0,2), however, the dose of 15,0μM was the best result of expansion (53,2%) and hatching (46,8%) (P=0,001). In experiment 3, the production of embryos was not influenced by supplementation with CLA (P=0,4), however, the dose of 150,0 μM resulted in higher rates of expansion (85,5%, P=0,001) and hatching (70,9%, P=0,001). In the experiment 4, the embryo production was not influenced by the supplementations (P=0,16), however the best result of the production was using 15,0μM of FO individually. The expansion and hatching rates was influenced by supplementation with the metabolism regulators added individually or in a combination (P=0,001). The best expansion rate was observed with the association CA+FO+CLA (90,05%), that was not different (P>0,05) of the CLA (86,4%) or CA+CLA (87,9%) groups. However, the best hatching rate was obtained with CLA (71,8%), which was higher to the other treatments (P=0.01). In conclusion, the use of the metabolic regulators CA, FO and CLA from the fourth day of the embryo culture in vitro increase ...